Drug and alcohol treatment providers' views about the disease model of addiction and its impact on clinical practice: A systematic review. (14th December 2017) - Barnett, Anthony I.; Hall, Wayne; Fry, Craig L.; Dilkes‐Frayne, Ella; Carter, Adrian
Abstract: Issues: Addiction treatment providers' views about the disease model of addiction (DMA), and their contemporary views about the brain disease model of addiction (BDMA), remain an understudied area. We systematically reviewed treatment providers' attitudes about the DMA/BDMA, examined factors associated with positive or negative attitudes and assessed their views on the potential clinical impact of both models. Approach: Pubmed, EMBASE, PsycINFO, CINAHL Plus and Sociological Abstracts were systematically searched. Original papers on treatment providers' views about the DMA/BDMA and its clinical impact were included. Studies focussing on tobacco, behavioural addictions or non‐Western populations were excluded. Key Findings: The 34 included studies were predominantly quantitative and conducted in the USA. Among mixed findings of treatment providers' support for the DMA, strong validity studies indicated treatment providers supported the disease concept and moral, free‐will or social models simultaneously. Support for the DMA was positively associated with treatment providers' age, year of qualification, certification status, religious beliefs, being in recovery and Alcoholics Anonymous attendance. Greater education was negatively associated with DMA support. Treatment providers identified potential positive (e.g. reduced stigma) and negative (e.g. increased sense of helplessness) impacts of the DMA on client behaviour. Implications/Conclusion: The review suggests treatment providers may endorse disease and other models while strategically deploying the DMA for presumed therapeutic benefits. Varying DMA support across workforces indicated service users may experience multiple and potentially contradictory explanations of addiction. Future policy development will benefit by considering how treatment providers adopt disease concepts in practice.